2019
DOI: 10.1590/s1980-6574201900020005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of walk training combined with blood flow restriction on resting heart rate variability and resting blood pressure in middle-aged men

Abstract: To investigate the effects of low-intensity walk training with and without blood flow restriction (BRF) on resting heart rate variability (HRV) and blood pressure (BP) in middle-aged men. Methods: Twenty-one men were randomly assigned into the walk training group with (BRF-W; n = 11) and without (NOR-W; n = 10) BFR. The resting HRV and blood pressure were assessed pre-and post-6 weeks of the intervention [3 times/week, 5 sets of 3-min walking (6 km.h-1) with 1-min of rest, totalizing 18 sessions of training]. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…More recently, Kambič et al (2019) observed a reduced systolic BP of patients with coronary artery disease following 8 weeks of knee extension BFR training (30-40% 1RM; 3 sets of 8-12 reps; 2x/week; BFRP ∼140 mmHg). Lastly, two studies verified an increase in HR variability (Ferreira Junior et al, 2019;Junior et al, 2019). Although literature is inconsistent, there is evidence to support that BFR training may reduce both HR and BP and increase HR variability in clinical populations.…”
Section: Arterial Compliance Stiffness and Diametermentioning
confidence: 91%
See 4 more Smart Citations
“…More recently, Kambič et al (2019) observed a reduced systolic BP of patients with coronary artery disease following 8 weeks of knee extension BFR training (30-40% 1RM; 3 sets of 8-12 reps; 2x/week; BFRP ∼140 mmHg). Lastly, two studies verified an increase in HR variability (Ferreira Junior et al, 2019;Junior et al, 2019). Although literature is inconsistent, there is evidence to support that BFR training may reduce both HR and BP and increase HR variability in clinical populations.…”
Section: Arterial Compliance Stiffness and Diametermentioning
confidence: 91%
“…Most included studies were performed with young adults, middle-aged and older adults, with or without clinical conditions, and used lower limb exercises (i.e., leg press, knee extension and flexion, or heel raises) ( Kim et al, 2009 ; Evans et al, 2010 ; Patterson and Ferguson, 2010 , 2011 ; Clark et al, 2011 ; Kacin and Strazar, 2011 ; Fahs et al, 2012 , 2014 ; Hunt et al, 2013 ; Yasuda et al, 2014 ; Kambič et al, 2019 ). Studies also used upper limb exercises (i.e., handgrip, elbow flexion, bench press, or triceps down) ( Credeur et al, 2010 ; Hunt et al, 2012 ; Ozaki et al, 2013 ; Yasuda et al, 2015b ; Cezar et al, 2016 ; Kim et al, 2017 ; Crisafulli et al, 2018 ) and treadmill walking ( Ferreira Junior et al, 2019 ; Junior et al, 2019 ). Importantly, many of the included studies had methodological limitations, such as failure in allocation concealment, blinding of participants and assessors; and intention-to-treat analysis ( Table 3 ).…”
Section: Is Cuff Pressure Adjusted In Blood Flow Restriction Training Interventions?mentioning
confidence: 99%
See 3 more Smart Citations